RECOMANDĂRILE METODOLOGICE ORIENTATE SPRE EVALUAREA ACTIVITĂȚII INCUBATOARELOR DE AFACERI AMPLASATE ÎN MEDIUL UNIVERSITAR - Mulic, Andrei; Ulian, Galina (CEP USM, 2020)
The purpose and objectives of the research lie in the elaboration and implementation of methodological recommendations for evaluating the efficiency of the operation of business incubators, taking into account the particularities of the university ecosystem.In order to achieve the objectives proposed during the paper we will use several research methods, in addition to the classical cognitive methods of analysis, observation, induction and deduction, we will also use the statistical method, comparison and description, prediction method and others. Results: in the presented material, methodological recommendations were developed aimed at evaluating the activities of business incubators located in a university environment. It also describes the mission and objectives of the business incubator as part of an ecosystem that accelerates technology transfer. The structure and range of services are presented, as well as the criteria for evaluating the activities of a business incubator operating within the university environment.
Keywords: entrepreneurship; innovation institutions from the Republic of Moldova; erformance indicators